Pseudosymblepharis perlongifolia (Bryophyta, Pottiaceae), a neglected species from Malaysia new for America - Alonso, Marta; Cano, María Jesús; Jiménez, Juan Antonio (Phytotaxa, 2014)
The Asian moss Pseudosymblepharis perlongifolia, previously known only from Malaysia, is reported for the first time for America on the basis of several collections from Maricao (Puerto Rico). The principal distinctive characters that separate it from the nearest species of Pseudosymblepharis and related genera are discussed. The species is described and illustrated.